IC 9087 Chromium-Chromite: Bureau Of Mines Assessment And Research - Proceedings Of Bureau Of Mines Briefing Held At Oregon State University, Corvallis, OR, June 4-5, 1985 (The National Institute for Occupational Safety and Health (NIOSH), 1986)
This briefing was sponsored by the Bureau of Mines to summarize ongoing and recently completed chromium-chromite research and resource assessment activities by the Bureau. Through the series of 18 presentations compiled herein, Bureau personnel covered a wide range of topics including U.S. chromite and chromium trends and usage patterns; foreign and domestic resources; and research activities on mineral characterization and beneficiation, chemical and pryometallurgical processing of chromite and chromium-bearing wastes, new low-chromium alloy and coating substitutes, corrosion- and oxidation-resistant stainless steels, and chromium-containing refractories.